TDP-43 Mutation Affects Stress Granule Dynamics in Differentiated NSC-34 Motoneuron-Like Cells - Ding, Qiao; Chaplin, Justin; Morris, Matthew J.; Hilliard, Massimo A.; Wolvetang, Ernst; Ng, Dominic C. H.; Noakes, Peter G. (Frontiers in Cell and Developmental Biology, 2021)
Amyotrophic Lateral Sclerosis (ALS) is characterized by degeneration of motor neurons in the brain and spinal cord. Cytoplasmic inclusions of TDP-43 are frequently reported in motor neurons of ALS patients. TDP-43 has also been shown to associate with stress granules (SGs), a complex of proteins and mRNAs formed in response to stress stimuli that temporarily sequester mRNA translation. The effect of pathogenic TDP-43 mutations within glycine-rich regions (where the majority of ALS-causing TDP-43 mutations occur) on SG dynamics in motor neurons is poorly understood. To address this issue, we generated murine NSC-34 cell lines that stably over-express wild type TDP-43 (TDP-43WT) or mutant forms (ALS-causing TDP-43 mutations TDP-43A315T or TDP-43M337V). We then differentiated these NSC-34 lines into motoneuron-like cells and evaluated SG formation and disassembly kinetics in response to oxidative or osmotic stress treatment. Wild type and mutant TDP-43 appeared to be largely retained in the nucleus following exposure to arsenite-induced oxidative stress. Upon arsenite removal, mutant TDP-43 clearly accumulated within HuR positive SGs in the cytoplasm, whereas TDP-43WT remained mostly within the nucleus. 24 h following arsenite removal, all SGs were disassembled in both wild type and mutant TDP-43 expressing cells. By contrast, we observed significant differences in the dynamics of mutant TDP-43 association with SGs in response to hyperosmotic stress. Specifically, in response to sorbitol treatment, TDP-43WT remained in the nucleus, whereas mutant TDP-43 relocalized to HuR positive SGs in the cytoplasm following exposure to sorbitol stress, resulting in a significant increase in TDP-43 SG numbers. These SGs remained assembled for 24 h following removal of sorbitol. Our data reveal that under certain stress conditions the rates of SG formation and disassembly is modulated by TDP-43 mutations associated with ALS, and suggest that this may be an early event in the seeding of insoluble cytoplasmic inclusions observed in ALS.